The impact of COVID-19 on Venezuelan migrants' access to health: A qualitative study in Colombian and Peruvian cities - Patricio Zambrano-Barragán; Sebastián Ramírez Hernández; Luisa Feline Freier; Marta Luzes; Rita Sobczyk; Alexander Rodríguez; Charles Beach (Elsevier, 2021)
This research seeks to understand how COVID-19 has affected access to healthcare among migrants in Latin American cities. Using ethnographic research methods, we engaged with Venezuelans living in conditions of informality in four Colombian cities-Barranquilla, Cucuta, Riohacha, and Soacha-and three Peruvian cities-Lima, Trujillo, and Tumbes. We conducted 130 interviews of both Venezuelan migrants and state and non-governmental actors within the healthcare ecosystems of these cities. We found that forced migrants from Venezuela in both Colombia and Peru face common obstacles along their access trajectories to healthcare, which we summarize as legal, financial, and relating to discrimination and information asymmetry. By limiting effective access to care during the pandemic, these obstacles have also affected migrants' ability to cover the costs of basic needs, particularly food and housing. Our study also found a prevalent reliance on alternative forms of care, such as telemedicine, easy-to-access pharmacies, and extralegal care networks. We conclude that COVID-19 has exacerbated preexisting conditions of informality and health inequities affecting Venezuelan migrants in Colombia and Peru.